ANALISIS PERTANGGUNG JAWABAN PELAKSANAAN KEWENANGAN MENEMBAK YANG DIMILIKI OLEH KEPOLISIAN NEGARA REPUBLIK INDONESIA - Rapilu, Muh. Guntur; Murary, Weron; Morintoh, Raymond R (Ensiklopedia Sosial Review, 2025)
Abstract: Police officers often have to deal with urgent situations, conditions, or problems, so it is necessary to use force, because criminal law legalizes every action from law enforcement officials against people suspected of committing criminal acts by depriving them of their freedom, but the police in making arrests are equipped with various authorities, one of which is the authority to shoot with firearms or more often known as authority shooting, but the act is allowed by laws and regulations with such conditions and procedures as have been regulated and stipulated by laws and regulations. The research method is a series of stages or systematic methods used to find the truth in a scientific work, in this case the writing of the final project, carried out in Fakfak Regency in accordance with the responsibility for the implementation of the shooting authority, the source of primary research materials in the form of; Basic norms, laws and regulations, secondary materials in the form of: literature books, legal research reports, written/scientific works related to the problems discussed, then conclusions are drawn and new data that support the research are found. The results of the research obtained from the implementation of shooting authority by members of the National Police of the Republic of Indonesia are regulated through several strict mechanisms and regulations, as regulated in Law Number 2 of 2002, the use of firearms must be based on the discretion of the police, in accordance with the code of ethics, reported administratively, and following the basic principles of the use of violence and firearms. All of this aims to ensure that these actions are carried out responsibly and in accordance with established procedures. These actions must be in accordance with the Regulation of the National Police Chief Number 8 of 2009 concerning the use of firearms, which is implemented with the aim of ensuring that the use of firearms by members of the police force is carried out responsibly and in accordance with procedures.Keywords: Accountability, Shooting, Police, Twilight of Fire